2022
DOI: 10.3390/healthcare10112206
|View full text |Cite
|
Sign up to set email alerts
|

Burdens of Apprentices Caused by the COVID-19 Pandemic and How They Deal with Them: A Qualitative Study Using Content Analysis One-Year Post-Breakout

Abstract: The COVID-19 pandemic resulted in a variety of burdens for apprentices and, as a result, in a need for resources to deal with them. The present study examined answers to two open-ended questions, which were part of a larger online survey about the burdens and resources during the pandemic from 1442 Austrian apprentices. Data collection took place from 29 March to 18 May 2021. The answers were analyzed with qualitative content analysis and revealed that most apprentices were burdened by pandemic-related restric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 59 publications
1
4
1
Order By: Relevance
“…from their general practitioner) is contradictory with previous findings (Haider et al, 2022) showing only around 3% of apprentices reported they actually consulted professional help, suggesting an intention-behaviour gap in seeking mental help (Tomczyk et al, 2020).…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations
“…from their general practitioner) is contradictory with previous findings (Haider et al, 2022) showing only around 3% of apprentices reported they actually consulted professional help, suggesting an intention-behaviour gap in seeking mental help (Tomczyk et al, 2020).…”
Section: Discussioncontrasting
confidence: 90%
“…In terms of resources, apprentices mostly seek help from their friends and family, but an important proportion reported they would also seek help from mental health professionals whereas workplace was not considered as a setting where to find help. This finding confirmed previous studies showing young people are more likely to seek help from their friends and for psychological and emotional problems than from other sources (Haider et al, 2022;. The proportion of apprentices reporting they would seek professional help (i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In Austria, mental health decreases were particularly apparent among young people as well [ 11 , 13 ]. Qualitative studies of Austrian school students and apprentices reported that young people suffered most from school-related concerns as well as from the pandemic-related restrictions and regulations, and limitations on their social contacts, while precisely those social contacts were perceived as the most important resources during the pandemic [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%